Family Education and Cultural Preservation Rurup Keeps Together The Saroinsong Raya Community In The Face Of Globalization - Terry, H (Journal of Educational Method and Technology, 2019)
The purpose of this study is to analyze the role of family education in preserving Rurup's culture in building togetherness in the Saroinsong Raya community in the era of globalization. The method used in this research is descriptive qualitative method, with the technique of collecting data and empirical facts directly in the field in order to obtain primary data, by means of observation, interviews, and documentation. Rurub culture research results can be used as a unifying tool to build community together in this globalization era, the family plays an important role in preserving the Rurup tradition handed down from parents to children as evidenced by the existence of the Rurup tradition which is still carried out until now.Â Keywords: Parents education; Rurubâ€™s culture; Globalization